2020
DOI: 10.4103/heartviews.heartviews_34_19
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular interventions to superficial femoral artery occlusion: Different approaches, technique, and follow-up

Abstract: Background: Superficial femoral artery lesion is one of the main causes for intermittent claudication or critical limb ischemia. Percutaneous transluminal angioplasty is one of the approved therapies for this medical entity. Anatomical factors should be considered in choosing the right approach and puncture. The purpose of this study is to discuss the anatomical, radiological, and technical factors which determine the preference of various approaches and to determine its safety, effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…High technical success rates were observed in both groups. In the ET group, 17 studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] reported technical success. An overall success rate of 92.52% (95% CI [89.08%, 94.94%]) was noted ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…High technical success rates were observed in both groups. In the ET group, 17 studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] reported technical success. An overall success rate of 92.52% (95% CI [89.08%, 94.94%]) was noted ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent need for surgery was reported in a few cases of ET. 10 studies [ 6 , 8 , 10 , 11 , 12 , 14 , 15 , 16 , 17 , 20 ] reported a need for further surgical interventions. Overall, 3.21% (95% CI [1.90%, 5.36%]) ( Figure 3 ) of the cases required conversion to open surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations